Microencapsulação de óleo de macadâmia para aplicação em misturas para bolo - Suzin, Mônica Araujo (2020)
The growing demand for foods that contain bioactive compounds or that present a formulation enriched with functional compounds makes food industries seek the development of new products that satisfy this new consumer audience. The formulation of products enriched with oils, which are a source of essential fatty acids, can be added to this search. The microencapsulation technique allows the protection of these oils against degradation, thus guaranteeing their oxidative stability and maintaining essential compounds. The present work aimed to microencapsulate macadamia oil by the method of hot homogenization for application in food products, such as cake mixes. The characterization of microparticles, carried out by means of analyzes such as DSC, FTIR, DRX and encapsulation efficiency, proved that the oil was correctly encapsulated and that there was an increase in the oxidative stability of macadamia oil, by means of Rancimat analysis. Macadamia oil was evaluated for its composition in fatty acids, in which the majority were oleic acid (57.51%), palmitoleic (15.33%), palmitic (9.44%) and linoleic (5.12 %). Nutritional quality indexes for fresh oil were calculated to assess the quality of macadamia oil in relation to atherogenicity and thrombogenicity indexes. Characterization analyzes for vanilla cake mixes containing 1 and 3% particles, based on instrumental analyzes of color, rheological behavior and texture, showed positive results for incorporation in these matrices. The characterization analyzes of the cake formulated with the addition of macadamia oil are important and decisive parameters for assessing possible consumer acceptance, since they influence their purchase decision and, therefore, a positive evaluation of the final product.